A quickscan pest risk analysis for the Meloidogyne mali - Pylypenko , L.A. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2016)
A quickscan pest risk analysis for the apple root-knot nematode Meloidogyne mali for the territory of Ukraine was performed. This assessment was initiated in response to the recent (2012/2013) interception of the apple root-knot nematode in the Netherlands and Italy and because of the species inclusion on the EPPO Alert List in 2014. The risk of M. mali introduction, establishment and economic impact in Ukraine was assessed as likely, which proved the need for specific statutory actions to be taken to prevent ingress of the apple root-knot nematode and mitigate its effects in Ukraine. It is stated that the detailed pest risk analysis is required.